Integrated hybrid model of sustainable supply chain in cement industry - Kiamars Fathi Hafshejani; Majid Bagheri Sorkhi; Mahmoud Modiri (مدیریت مهندسی و رایانش نرم, 2023)
In this research, by studying the research background and using the latest version of SCOR model and experts' opinion, while identifying the factors affecting supply chain stability and determining the weight of each factor by IVHF-DANP method, the priority of SSCM rings has been determined using EHFL-VIKOR method in cement industry with the aim of improving supply chain performance. Consequently, in addition to six criteria of SCOR model and three dimensions of sustainability approach, ten other factors have been determined by experts and in total, the weight of nineteen factors has been determined and the customer's interest ring has the most preference. Then, the relevant mathematical model was presented and solved in GAMS software using NSGA-II method in MATLAB software. The combined integrated model of sustainable supply chain has been dealt with in this research since the whole supply chain -from the primary supplier to the final customer- is considered in forming and solving the model and each of the objective functions has been realized by assigning the characteristics of the SCOR model to the three dimensions of the sustainability approach formed accordingly.